Plasmonic properties of gold nanospheres coupled to reduced graphene oxide for biosensing applications - Fantoni, Alessandro (2019)
Graphene-based materials have been extensively explored in recent years as valuable candidates as the key material for novel structures in the field, among many other applications, of sensing devices. Reduced Graphene Oxide (rGO) is a type of chemically derived graphene, with equivalent optical properties but easier to be synthetized. This work reports a study about the applicability of rGO as a support for gold nanoparticles (AuNPs). The resulting AuNPs-rGO composites are studied in terms of spectral light transmission and plasmonic resonance as a possible sensing element for a photonic protein sensor device.